Electrochemical corrosion protection of neat and zinc phosphate modified epoxy coating: A comparative physical aging study on Al alloy 6101 - Khan, Ahsan Riaz; Zhang, Hai-Jun; Jun, Zhang; Maosheng, Zheng; Eldin, Sayed M.; Siddique, Imran (Frontiers in Chemistry, 2023)
Optimizing the pigment volume concentration of zinc phosphate pigments can protect Al alloy 6101 from alkaline media. Additionally, zinc phosphate pigments form a shielding film on the substrate and facilitate stopping the penetration of aggressive corrosion ions. The efficiency of eco-friendly zinc phosphate pigments is almost 98% during the corrosion analysis. A comparative study of physical aging of neat epoxy and Zinc Phosphate (ZP) pigment-modified epoxy coatings on Al alloy 6101 was conducted in Xi'an, China, for one year in all four seasons, where in summer for 3 months, results degraded more due to high UV radiation and humidity; it is found that peeling force of ZP pigments modified epoxy coatings is 50% higher of than that of the neat epoxy coatings though both peel-off adhesion strength and scratch test visibility decreased in both coatings; The electrochemical resistance of ZP pigments modified epoxy coatings is about 30% higher of than that of neat epoxy coatings, the corrosion rate of ZP pigments modified epoxy coatings is about 70% lower of than that of neat epoxy coatings, moreover the gloss retention is 20% higher in the modified epoxy; Optical surface observation of the coatings showed that the ZP modified epoxy coating could effectively restrict the crack and shrinkage in coatings after aging experimentation in the natural environment.